Estrategias de afrontamiento para el estrés en voluntarios de la Cruz Roja Colombiana U.M Cartago - Melissa, Berrío (Universidad Antonio Nariño, 2023)
Mental health is a state of well-being of the human being in its integral axis as a person, for which is not the absence of a disease at some point in life may be prone to care needs. One of the warning signs of the mental health is the stress it can be a pathology where the human being is in situations of threats or high demand.